(untitled) (Socio-economic relations in the digital society, 2019)
We consider the problem of electing a diagnostic of the levels of formation of economic competence of future specialists. Research material was a publication which features of economic training of students non-economists. It substantiates the key principles of election of the diagnostic levels of formation of economic competence of students of chemical-technological specialties that relate to statistical reliability guide to the names, consistency with the structure of economic competence, the adequacy of the system properties.